Efficacy and economics of rodenticides for rodent management in watermelon (Citrullus lanatus) fields - SINGH, PARMESH; PASAHAN, S C; SABHLOK, V P; SINGAL, R K (The Indian Journal of Agricultural Sciences, 2013)
Efficacy and economics of single and double application of 2% zinc phosphide and 0.005% bromadiolone baits for rodent control in watermelon [Citrullus lanatus (Thunb.) Mansf & Nakai] fields were determined-during summer 1994 in and around Risar (Haryana). Double baiting with zinc phosphide followed by bromadiolone after 3 days, bromadiolone followed by zinc phosphide after 7 days and bromadiolone followed by another bromadiolone baiting after 7 days resulted in signiticantly (P < 0.05) highe reduction of rodent population than with single application of any of these rodenticides. the rodenticidal treatments saved yield loss ofÂ 199-1 996 kg/ha, resulting in cost: benefit ratio of 1: 66-1 :90. Application of bromadiolone bait followed by another bromadio lone bait was the most economical combination.